Austenland [videorecording (DVD)] - Hess, Jerusha; Seymour, Jane, 1951-; Russell, Keri, 1976-; Coolidge, Jennifer; Feild, J. J.; McKenzie, Bret; King, Georgia, 1986-; Whittle, Ricky, 1981-; Callis, James; Vansittart, Rupert; Hale, Shannon (Sony Pictures Home Entertainment, 2013)
Jane Hayes's adoration of all things Jane Austen is complicating her love life. Determined to be the heroine of her own story, Jane spends her life savings on a trip to Austenland, an eccentric Austen-inspired resort, where she meets two very different gentlemen, but has a difficult time determining where fantasy ends and real life, and maybe even love, begins.